Measurement of Bose–Einstein correlations in e+e− → W+W− at √s ≃ 189 GeV - Dova, María Teresa (2000)
We investigate Bose–Einstein correlations (BEC) in W-pair production at √s ≃ 189 GeV using the L3 detector at LEP. We observe BEC between particles from a single W decay in good agreement with those from a light-quark Z decay sample. We investigate their possible existence between particles coming from different W’s. No evidence for such inter-W BEC is found.